The Founders on Citizenship and Immigration: Principles and Challenges in America - Erler, Edward J.; Marini, John; West, Thomas G. (Rowman & Littlefield Publishers, 2007)
Working with the underlying premise that America's founding principles continue to be vital in the modern era, Erler, Marini, and West take a conservative look at immigration, one of today's most pressing political issues. Character_the capacity to live a life befitting republican citizens_is, as the Founders knew, crucial to the debate about immigration. The Founders on Citizenship and Immigration seeks to revive the issue of republican character in the current immigration debate and to elucidate the constitutional foundations of American citizenship. Published in cooperation with the Claremont Institute.